Prostacyclin receptor agonist selexipag in a patient with high-risk idiopathic pulmonary arterial hypertension: a case report - E. A. Rezukhina; O. V. Rodnenkov; T. V. Martynyuk (Кардиоваскулярная терапия и профилактика, 2021)
We present a 48-year-old patient with World Health Organization class III idiopathic pulmonary arterial hypertension (IPAH), taking specific therapy with macitentan 10 mg a day, who was readmitted to the National Medical Research Center of Cardiology due to increase in exercise dyspnea and decrease in effort tolerance. According to a comprehensive examination, single factors of high risk and unfavorable prognosis were identified. Due to systemic hypotension when using inhaled iloprost, selexipag was added to therapy. According to control hospitalization, 8-month selexipag therapy improved the patient's condition, as well as high risk factors were not revealed. Selexipag is a selective oral prostacyclin receptor agonist recommended for longterm IPAH therapy in adult patients.